MEDIASI SEBAGAI BASIS DALAM PENYELESAIAN PERKARA PIDANA - Agus Raharjo (Fakultas Hukum Universitas Gadjah Mada, 2008)
Litigation model on criminal justice process can’t give satisfy and justice to offender and victim crime, so must be reform. Criminal Justice System is a network of criminal justice by using criminal law as ultimate material. The resolution of criminal cases at the time in Indonesia based on KUHAP (Act No. 8/1981) is recognized as litigation model. On KUHAP, non litigation model on criminal cases resolution is unknown, but based data research in Central Java, we are concluding that criminal cases resolution through non litigation model can be enable in Indonesia. For offender and victim, they can look for by way and place other. Non litigation model of criminal cases resolution can answer weakness on litigation model and show that existence of justice in many room; and according to pluralism in our constitutional, this model ought to accommodate in criminal justice system.